Meteor stream identification: a new approach. Application to 3675 radio meteors - Jopek, T.J.; Valsecchi, G.B.; Froeschle, Cl. (Astronomical Institute of the Slovak Academy of Sciences, 1999)
The new criterion DN for meteoroid streams identification, based on variables directly linked to observations, was applied to a set of radio meteors observed in Adelaide. 28 streams, combinning 28% of the 3675 orbits have been detected. 8 streams have a single crossing point with the Earth orbit, 20 groups were identified as twin showers.
Keywords: Adelaide radio meteors; meteor streams searching